Trade marketing para impulsar la venta de productos de consumo en máquinas vending de barexpress para la escuela superior politécnica del Litoral - Garófalo Gaibor, Leandro (2017)
Trade Marketing is a marketing tool that seeks to develop and implement effective management between the supplier and the distributor of products or services to a mutual benefit, ultimately resulting in the consumer; Is born of an alliance with the purpose of stimulating in a very productive way the final demand. Its appearance was in the 90's, according to Santemases in 1998, its first management was with the Colgate-Palmolive business group, who managed to conceive that the producer should be considered as a natural partner in the management of the distributor; Although it is true, the collaborative system existed, but the way to plan the logistics, market support and other aspects of this discipline, have been created from its appearance…..